2013
DOI: 10.1093/carcin/bgt034
|View full text |Cite
|
Sign up to set email alerts
|

The yin and yang of nitric oxide in cancer progression

Abstract: Nitric oxide (NO) is a short-lived, pleiotropic molecule that affects numerous critical functions in the body. Presently, there are markedly conflicting findings in the literature regarding NO and its role in carcinogenesis and tumor progression. NO has been shown to have dichotomous effects on cellular proliferation, apoptosis, migration, invasion, angiogenesis and many other important processes in cancer biology. It has been shown to be both pro- and antitumorigenic, depending on the concentration and the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
286
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(310 citation statements)
references
References 137 publications
3
286
0
1
Order By: Relevance
“…Unfortunately, these assays only make an approximation of the NO level within a solution, a problem that has led researchers to find contradictory results when comparing the predicted NO levels through different analysis methods [60]. sulfanilamide in phosphoric acid and then N-1-napthylethylenediamine dihydrochloride to the samples of interest, as depicted in Figure 2 [59].…”
Section: Upstream and Downstream Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, these assays only make an approximation of the NO level within a solution, a problem that has led researchers to find contradictory results when comparing the predicted NO levels through different analysis methods [60]. sulfanilamide in phosphoric acid and then N-1-napthylethylenediamine dihydrochloride to the samples of interest, as depicted in Figure 2 [59].…”
Section: Upstream and Downstream Measurementsmentioning
confidence: 99%
“…The Griess method uses standard biology-and chemistry-based methods in combination with instruments that are commercially available. Unfortunately, these assays only make an approximation of the NO level within a solution, a problem that has led researchers to find contradictory results when comparing the predicted NO levels through different analysis methods [60]. An alternate method of predicting NO concentration within a system is performed by examining upstream components such as NOS activity.…”
Section: Upstream and Downstream Measurementsmentioning
confidence: 99%
“…DDAH-2 functionsas an inhibitor of nitric oxide (NO) synthase. NO overexpression has been reported in various tumors, including lung cancer, and its inhibition is regarded as an anticancer therapy (28). Cancer cells are able to evade cell cycle arrest via VHR overexpression (29).…”
Section: Discussionmentioning
confidence: 99%
“…57,58 Dichotomous effects of NO have been observed on important processes of cancer biology such as proliferation, apoptosis, migration, invasion, and angiogenesis. 59 Nevertheless, it has been shown that NO effects depend on the source and concentration of the gas in the tumor area, affecting the cancer and surrounding cells. 58 In cancer models, low levels of NO (,100 nM) generated by eNOS increase proliferation and angiogenesis, and higher levels of NO produced by iNOS (.500 nM) cause DNA damage, oxidative stress, cytotoxicity, and apoptosis of cancer cells.…”
Section: Drewes Et Almentioning
confidence: 99%